2017
DOI: 10.1097/aln.0000000000001576
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Chronic Pain after Thoracic Surgery

Abstract: Background The goal of this study was to detect the predictors of chronic pain at 6 months after thoracic surgery from a comprehensive evaluation of demographic, psychosocial, and surgical factors. Methods Thoracic surgery patients were enrolled 1 week before surgery and followed up 6 months postsurgery in this prospective, observational study. Comprehensive psychosocial measurements were assessed before surgery. The presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
198
4
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 210 publications
(219 citation statements)
references
References 51 publications
14
198
4
3
Order By: Relevance
“…Experts currently suggest that aggressive treatment of acute pain may have potential benefits in preventing the transition to persistent postsurgical pain. [30][31][32] …”
Section: Evaluating the Role Of New Interfascial Plane Blocksmentioning
confidence: 99%
“…Experts currently suggest that aggressive treatment of acute pain may have potential benefits in preventing the transition to persistent postsurgical pain. [30][31][32] …”
Section: Evaluating the Role Of New Interfascial Plane Blocksmentioning
confidence: 99%
“…Chronic pain is one of the most common health problems and it is known that approximately 22.5% of chronic pain is secondary to surgical procedures [12]. Although the prevalence of PTPS after thoracic surgery ranged from 14% to 83% [14], the incidence of PTPS neuropathic pain ranged from 35 to 83% and neuropathic pain is associated with more severe chronic pain [15,16].…”
Section: Prevalencementioning
confidence: 99%
“…Only 5% of patients develop severe pain and disability-related difficulties in daily living activities [1,4,5,11]. One study reported that 27% of patients described chronic pain at 6 months post-thoracotomy and 8.2% had pain at a level that limited their daily activities [12]. Approximately half of the patients describe persistent thoracotomy pain between the first and second years after surgery and 30% between the fourth and fifth years [5,13].…”
Section: Introductionmentioning
confidence: 99%
“…We appreciate Holm et al 's interest in our paper (1). By design, our study was not powered to answer each secondary result.…”
mentioning
confidence: 99%